Survey of the knowledge of elderly people regarding non-conventional food plant - QUERINO, Elisangela Rodrigues (130, 2024)
The acronym PANC refers to all plants that have one or more edible parts, whether they are spontaneous or cultivated, native or exotic, and are not included in our daily diet. Non-Conventional Edible Plants (PANC) are vegetables that have been known and used for many years in indigenous culture, but which have ceased to be prominent today, being underutilized by the population. Brazil currently has one of the greatest biodiversity in the world, however, the plant species used in food are still scarce. However, despite the numerous benefits, it is mainly due to the lack of knowledge of the majority of the Brazilian population, even though some individuals, mostly elderly, associate PANC with their food consumption in childhood. Studies have found that the elderly have a great deal of knowledge about non-conventional edible plants, but doubts and myths about them can be noted, and it is necessary to demystify them. In view of the above, a survey was conducted with the aim of assessing the knowledge of elderly people regarding unconventional food plants, their consumption and cultivation methods. The questionnaire was administered in person to 97 elderly people over a two-year period. The results obtained were calculated as percentages using the Google Sheets tool and compared with interviews conducted by other authors using articles published in online databases. The Scielo and Google Scholar databases were used for the search. Based on this study, we can conclude that most of the interviewees know about and have consumed PANC in some way, but the minority uses them.

RESUMO: A sigla PANC refere-se a todas as plantas que possuem uma ou mais partes comestíveis, sejam elas espontâneos ou cultivados, nativos ou exóticos, e não fazem parte da nossa alimentação diária. Plantas alimentícias não convencionais (PANC) são hortaliças conhecidas e utilizadas há muitos anos na cultura indígena. cultura, mas que hoje deixaram de ter destaque, sendo subutilizadas pela população. Brasil atualmente possui uma das maiores biodiversidades do mundo, porém, as espécies vegetais utilizadas na alimentação são ainda escasso. Contudo, apesar dos inúmeros benefícios, isso se deve principalmente à falta de conhecimento do maioria da população brasileira, embora alguns indivíduos, em sua maioria idosos, associem PANC com o consumo alimentar na infância. Estudos descobriram que os idosos têm uma grande quantidade de conhecimento sobre plantas comestíveis não convencionais, mas podem-se notar dúvidas e mitos sobre elas, e é é necessário desmistificá-los. Diante do exposto, foi realizada uma pesquisa com o objetivo de avaliar o conhecimento dos idosos sobre as plantas alimentícias não convencionais, seu consumo e métodos de cultivo. O questionário foi aplicado pessoalmente a 97 idosos durante um período de dois anos. período. Os resultados obtidos foram calculados em porcentagens através da ferramenta Planilhas Google e comparados com entrevistas realizadas por outros autores utilizando artigos publicados em bases de dados online. O Scielo e as bases de dados do Google Scholar foram utilizadas para a busca. Com base neste estudo, podemos concluir que a maior parte os entrevistados conhecem e já consumiram PANC de alguma forma, mas a minoria utiliza.
Levantamento do conhecimento de idosos sobre plantas alimentícias não convencionais
Publicado em: International Journal of Development Research Vol. 14, Issue, 09, pp. 66540-66542, September, 2024 https://doi.org/10.37118/ijdr.28653.09.2024
Keywords: Plantas comestíveis; Alimentos não convencionais; Produção Alimentícia